2016
DOI: 10.1016/j.jaci.2015.07.051
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell hyporesponsiveness and impaired development in a CD247-deficient patient

Abstract: The agencies that provided financial support for the conduct of the research and preparation of the article played no role in the study design; in the collection, analysis and interpretation of data; in the writing of the report, or in the decision to submit the article for publication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…It has previously been reported that cell surface expression of the CD16A receptor depends on a noncovalent association with the signaling dimers FceR1γ and/or CD247 (2)(3)(4). Ex vivo analysis of CD16A cell surface expression on primary human NK cells deficient in either FceR1γ or CD247 has suggested that CD16A does not discriminate between these adaptor molecules (15), and we confirmed these data in vitro when fibroblasts were transfected with CD16A alone or in combination with either FceR1γ or CD247 adaptor molecules. Only small amounts of CD16A protein, which correspond to an immature (EndoH-sensitive) species, were detected in cells transfected with the receptor construct alone (Fig.…”
Section: Cd16asupporting
confidence: 85%
See 1 more Smart Citation
“…It has previously been reported that cell surface expression of the CD16A receptor depends on a noncovalent association with the signaling dimers FceR1γ and/or CD247 (2)(3)(4). Ex vivo analysis of CD16A cell surface expression on primary human NK cells deficient in either FceR1γ or CD247 has suggested that CD16A does not discriminate between these adaptor molecules (15), and we confirmed these data in vitro when fibroblasts were transfected with CD16A alone or in combination with either FceR1γ or CD247 adaptor molecules. Only small amounts of CD16A protein, which correspond to an immature (EndoH-sensitive) species, were detected in cells transfected with the receptor construct alone (Fig.…”
Section: Cd16asupporting
confidence: 85%
“…It therefore seems likely that the major factors influencing whether CD16A associates with CD247 or FceR1γ are related to the relative levels of expression of the different adaptors and possible competition from other receptors that also bind CD247 and FceR1γ. For example, a population of terminally differentiated human NK cells lose expression of FceR1γ (31), and, in these cells, CD16A associates exclusively with CD247 (15). In contrast, the majority of circulating human NK cells express both FceR1γ and CD247, but they also express multiple NK receptors that associate with these adaptor molecules.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only two of these genes have been suggested to play a role in allergic disease through functional studies: USF1 80 and STARD3 81 . However, many have a known function ( Supplementary Table 10 ) that is directly relevant to allergic disease pathophysiology, such as F11R 82 , 83 , MICB 84 , CD247 85 , 86 , PGAP3 87 , AAGAB , 88 CAMK4 89 and PEX14 90 . In summary, of the 49 likely target genes of published asthma risk variants, only 16 were previously implicated by functional studies in disease pathophysiology.…”
Section: Do Any Of the Likely Target Genes Represent Potential New Plmentioning
confidence: 99%
“…1 Regarding B cells, the role of NF-kB1 was underlined in a murine nf-kb1 knockout model in which peripheral B cells showed defective maturation, defective isotype switching, and impaired humoral immune responses. [1][2][3] A similar, although more pronounced, immunologic phenotype was observed in the nf-kb2 knockout mice, with defective secondary lymphoid organ development and impaired B-cell development both in early (bone marrow) and in late (periphery) stages with defective humoral responses both to T-dependent and to T-independent antigens. 1 The role of NF-kB2 in human B-cell development was recently defined in patients carrying monoallelic mutations in NF-kB2, leading to common variable immunodeficiency (CVID)-like disease with autoimmunity and defects in late stages of peripheral B-cell maturation.…”
mentioning
confidence: 57%